Effectiveness of Baby Massage with Lavender Telon Oil on Infant Sleep Quality in Ciseureuh, Purwakarta (July–August 2024) - Febriana, Rositta; Yuliani , Susanti (CV. Publikasi Indonesia, 2025)
Sleep is a vital physiological need for infant growth and development. Its quality depends not only on duration but also on the restorative benefits gained during rest. In Indonesia, infant sleep disorders remain common, while parental awareness is still limited. A simple non-pharmacological intervention is infant massage with lavender telon oil, which contains linalool and linalool acetate, known for their calming effects. This research aims to evaluate the effectiveness of infant massage with lavender telon oil on the sleep quality of infants aged 3–12 months at the Ciseureuh Village Posyandu, Purwakarta District. The research applied a quantitative approach using a pre-experimental one-group pre-test post-test design. The study population consisted of 32 infants aged 3–12 months, recruited through a total sampling technique. Data were collected using a validated and reliable questionnaire. Statistical analysis with a paired t-test showed a significant difference in infant sleep quality before and after the massage, with a p-value of 0.000 (<0.05). These findings confirm that infant massage with lavender telon oil effectively improves sleep quality in infants. In conclusion, infant massage using lavender telon oil can serve as a simple, safe, and affordable intervention to enhance sleep quality. The results of this study are expected to provide valuable insights for healthcare providers, community health workers, and parents in promoting optimal infant growth and development through effective, non-invasive strategies.